Water and wastewater engineering : design principles and practice. ([Place of publication not identifed] : [publisher not identified], 2021)
The book contains the complete procedure of industrial wastewater treatment and disposal at common effluent treatment plant at colony industrial area in Delhi, India.
The term "Wastewater"-- Wastewater Treatment System -- Industrial Wastewater Treatment -- Common Effluent Treatment Plan -- Design Basis/Considerations for CETP -- Jhilmil and friends colony CETP -- Treatment Philosophy at Jhilmil CETP -- Treatment Processes at Jhilmil CETP -- Process Scheme at Jhilmil and friends Colony CETP -- Laboratory Analysis -- Wastewater Testing Procedure (Physico-Chemical Analysis) -- Practical Work -- Appendix -- A: Treated Effluent Quality Standards foCETPs -- Bibliography.
Includes bibliographical references.
Keywords: WATER-SUPPLY